Do new sea spray aerosol source functions improve the results of a regional aerosol model?. (1st February 2019) - Barthel, Stefan; Tegen, Ina; Wolke, Ralf
Abstract: Sea spray aerosol particle is a dominating part of the global aerosol mass load of natural origin. Thus, it strongly influences the atmospheric radiation balance and cloud properties especially over the oceans. Uncertainties of the estimated climate impacts by this aerosol type are partly caused by the uncertainties in the particle size dependent emission fluxes of sea spray aerosol particle. We present simulations with a regional aerosol transport model system in two domains, for three months and compared the model results to measurements at four stations using various sea spray aerosol particle source source functions. Despite these limitations we found the results using different source functions are within the range of most model uncertainties. Especially the model's ability to produce realistic wind speeds is crucial. Furthermore, the model results are more affected by a function correcting the emission flux for the effect of the sea surface temperature than by the use of different source functions. Highlights: Effect of SST can be higher than differences between source functions. Differences between source functions can be smaller than current uncertainties. Main uncertainty is model performance of surface wind speed.